When Care Becomes Cruel: A Phenomenological Perspective on Educators’ Struggles Amidst Underfunding in Public Education - Parker, Lana; Stuart-Hitchcox, Holt (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2025)
Drawing on our empirical study engaging focus groups of highly experienced educators and stakeholders (n = 12) in Ontario, Canada, we examine the cruel refiguration of educational worker care under neoliberalism in public education. Austerity policies have degraded conditions in the schools such that educators are unable to fulfill their attachments to education as a public good. In addition, the neoliberal individualization of responsibility asks workers to address worsening conditions as individuals, collapsing structures of solidarity. In this paper, we explore the phenomenological aspects of how neoliberal individualism structures educator moods, examining educators’ affective interplays of grief, rage, despair, determination, and exhaustion as they struggle to independently uphold or repair a system under duress. We argue that neoliberal conceptions of care are insufficient—and indeed Sisyphean—as singular efforts cannot address the current widespread systemic problems. Instead, we suggest educational workers should disavow individualism, refusing to bear personal responsibility for systemic issues, and should instead seek broader, collective organization against further neoliberal education reforms.